FACTORS WICH INFLUENCE THE NUTRITION STATUS TODDLERON MOTHER JOB STATUS IN REGION OF PUSKESMAS LANGSA BARAT LANGSA CITY 2018 - Dewita (JURNAL KESEHATAN ALMUSLIM, 2019)
The problem of the cause of death of children under five in the world is malnutrition, amounting to 45%, including cases of stunting, underweight and acute malnutrition caused by socio-economic conditions. Research Objectives To determine the Factors Affecting Toddler Nutritional Status Based on the Job Status of Mothers in the Langsa West Langsa Working Area in 2018. The method is analytical with Cross Sectional design. The population in this study were all mothers of children under five (12-59 months) and toddlers in the Work Area of West Langsa Health Center, Langsa City, amounting to 1110 people. The sampling technique in this study used the Proportional Stratified Sample formula totaling 100 samples. Data collection using questionnaires, data analyzed by univariate and bivariate by using frequency distribution tables, cross tables and statistical and narrative tests. The results showed that respondents with good nutritional status (75%), the results of statistical tests with the chi-square test found the influence of nutritional status of children with maternal knowledge, this can be seen from ρ value = 0.00 <0.05 and the influence of nutritional status toddlers with family socioeconomic status with ρ value = 0.029 <0.05 while there was no influence of under-fives nutrition status on the work of mothers with ρ value = 0.059> 0.05. Suggestions are very much needed for the role of health workers to be able to provide information about health programs, especially regarding the nutritional status of children through counseling activities to the community, so that existing knowledge in the community, especially mothers of children under five become better.